Truth, trust, and sanctions: On institutional selection in sender-receiver games - Ronald Peeters; Marc Vorsatz; Markus Walzl (University of Innsbruck, Research Platform Empirical and Experimental Economics (eeecon), 2011)
We conduct a laboratory experiment to investigate the impact of institutions and institutional choice on truth-telling and trust in sender-receiver games. We find that in an institution with sanctioning opportunities, receivers sanction predominantly after having trusted lies. Individuals who sanction are responsible for truth-telling beyond standard equilibrium predictions and are more likely to choose the sanctioning institution. Sanctioning and non-sanctioning institutions coexist if their choice is endogenous and the former shows a higher level of truth-telling but lower material payoffs. It is shown that our experimental findings are consistent with the equilibrium analysis of a logit agent quantal response equilibrium with two distinct groups of individuals: one consisting of subjects who perceive non-monetary lying costs as senders and non-monetary costs when being lied to as receivers and one consisting of payoff maximizers.
Keywords: C91; C92; 330; Experiment; Sender-receiver games; Strategic information transmission; Institutional selection; Nichtkooperatives Spiel; Vertrauen; Soziale Norm; Psychologie; Dynamisches Spiel; Theorie